2023
DOI: 10.5614/jpwk.2022.33.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of Walking in Campus Landscape to Young Adults

Abstract: Green space has a vital role in the community’s health and well-being. Forest bathing is an effective method of enjoying the forest atmosphere through physical activity or relaxing in a forest landscape. However, until now, no one has declared the benefits of forest therapy in Indonesia. This study clarifies the physiological and psychological effects of walking in a campus landscape. This research was conducted using experimental methods through physical activity survey, self-report questionnaires, Visitor Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…In the present systematic literature review, 7 articles involved in visit frequency of campus green space or the duration of campus green space use (Holt et al, 2019;Stepansky et al, 2022;Lee et al, 2022;Ning et al, 2023;Pratiwi et al, 2022a;Zhang et al, 2023). However, 3 experimental design studies failed to regard the duration of campus green space use as a variable (Ning et al, 2023;Pratiwi et al, 2022a;Zhang et al, 2023). 3 studies involved in visit frequency Holt et al, 2019;Lee et al (2022) and 1 studies simultaneously involved in visit frequency and duration .…”
Section: Exposure To University Campus Green Space and Students' Ment...mentioning
confidence: 81%
See 3 more Smart Citations
“…In the present systematic literature review, 7 articles involved in visit frequency of campus green space or the duration of campus green space use (Holt et al, 2019;Stepansky et al, 2022;Lee et al, 2022;Ning et al, 2023;Pratiwi et al, 2022a;Zhang et al, 2023). However, 3 experimental design studies failed to regard the duration of campus green space use as a variable (Ning et al, 2023;Pratiwi et al, 2022a;Zhang et al, 2023). 3 studies involved in visit frequency Holt et al, 2019;Lee et al (2022) and 1 studies simultaneously involved in visit frequency and duration .…”
Section: Exposure To University Campus Green Space and Students' Ment...mentioning
confidence: 81%
“…Overall, the results indicated that all types of campus green space were beneficial for university students' mental health and well-being compared with hard landscape. The benefits included more psychological restoration Sun et al ( 2021 2023), less negative moods (Pratiwi et al, 2022a;Pratiwi et al, 2022a;Guo et al, 2020). In addition, blue space and waterfront space which is dominated by the water landscape element had better restorative effects than other landscape types such as vegetation space, courtyard space and forest space Ning et al, 2023;Sun et al, 2021;Lu & Fu, 2019).…”
Section: Landscape Types Of University Campus Green Space and Univers...mentioning
confidence: 98%
See 2 more Smart Citations
“…In Barcelona, a hands-on investigation of the total green space environment in which elementary school students in grades 2-4 live and learn demonstrated that the greenness of the space was associated with children's emotional well-being (34); and in New Zealand, the effects of blue, green, and biodiversity on adolescents' mental and emotional wellbeing were assessed in a community setting, and the results showed a positive correlation between the two (35). Through combing through the literature, we found that the research population focuses on children (36), college student groups (37), and older adults (38), while little research has been done on young urban residents aged 18-35 in China, which we would like to know. Moreover, the current research has explored the restorative effects of natural elements in blue space and green space on emotional health (39), while ignoring the connection between other objective conditions and the subject's own use of the green space and emotional health.…”
Section: Emotional Well-being and Green Spacementioning
confidence: 99%